Representasi Kesejahteraan Masyarakat Bali dalam Kebijakan Upah Minimum - Jainani Sures,; Marvelia Merquis Wibowo ,; Marsya Fidyana Hidayat , (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the representation of Balinese people's welfare in the formulation and implementation of minimum wage policy. Using a qualitative descriptive approach, the study analyzes policy documents, stakeholder perspectives, and socioeconomic indicators to understand how minimum wage decisions reflect the lived realities of Balinese workers. Findings indicate that although minimum wage adjustments aim to improve welfare, there is a gap between policy expectations and actual economic conditions, particularly in sectors heavily dependent on tourism. Customary obligations and the high cost of living also influence perceptions of wage adequacy. This study emphasizes the need for more participatory policy formulation and more contextual welfare assessments to ensure wage policies align with community needs.